2008
DOI: 10.1080/10942910701573024
|View full text |Cite
|
Sign up to set email alerts
|

Geometric and Mechanical Properties of Mung Bean (Vigna RadiataL.) Grain: Effect of Moisture

Abstract: In this research, selected geometric and mechanical properties of mung bean grain were evaluated as a function of moisture content. Five levels of moisture content ranging from 7.28 to 17.77% d.b. (dry basis) were used. The average length, width, thickness, arithmetic and geometric mean diameters, sphericity, thousand grain mass and angle of repose ranged from 5.145 to 6.199 mm, 3.760 to 4.474 mm, 3.537 to 4.223 mm, 4.147 to 4.965 mm, 4.090 to 4.893 mm, 0.795 to 0.789, 52.3 to 64.6 g, and 25.87 to 29.38° as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
37
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 33 publications
(121 reference statements)
8
37
2
Order By: Relevance
“…The arithmetic and geometric diameters were smaller than the length and greater than the width and thickness. Baümler, Cuniberti, Nolasco, and Riccobene (2006), Unal et al (2008), Ashtiani Araghi, Sadeghi, and Hemmat (2010), Gharibzahedi et al (2011), Ilori et al (2011 and Kaliniewicz et al (2015) found similar results for safflower, mung bean, rough rice, red lentil, Mexican sunflower and buckwheat seeds, respectively. The importance of these and other characteristic axial dimensions for determining aperture size and other parameters in machine design have been discussed by Mohsenin (1986).…”
Section: Resultssupporting
confidence: 67%
See 4 more Smart Citations
“…The arithmetic and geometric diameters were smaller than the length and greater than the width and thickness. Baümler, Cuniberti, Nolasco, and Riccobene (2006), Unal et al (2008), Ashtiani Araghi, Sadeghi, and Hemmat (2010), Gharibzahedi et al (2011), Ilori et al (2011 and Kaliniewicz et al (2015) found similar results for safflower, mung bean, rough rice, red lentil, Mexican sunflower and buckwheat seeds, respectively. The importance of these and other characteristic axial dimensions for determining aperture size and other parameters in machine design have been discussed by Mohsenin (1986).…”
Section: Resultssupporting
confidence: 67%
“…This confirms the fact that the seeds are spherical or oval in shape, enabling the grains to roll. The measured angle of repose was considerably lower than that reported for rough rice (Ashtiani Araghi et al, 2010), mung bean (Unal et al, 2008) and lentil (Amin et al, 2004) and similar to that reported for buckwheat grain (Parde et al, 2003) and sorghum seed (Mwithiga & Sifuna, 2006). This may be due to the smoother surface or shape factor of buckwheat that imposes resistance to the seeds in sliding on one another.…”
Section: Angle Of Repose and Frictional Properties Of Buckwheat Grainscontrasting
confidence: 46%
See 3 more Smart Citations